Problematika Pemahaman Teks Narasi Pada Siswa Kelas 4 SDN Margorejo 1/403 Surabaya - Diki Ardiyanto; Ida Sulistyawati; Via Yustitia (Universitas PGRI Adi Buana Surabaya, 2021)
Understanding narrative text is an urgency for students. Reading is not just about seeing symbols, but understanding the meaning of those symbols. This research is used to find problems or problems in understanding narrative text reading. The purpose of this study is to describe the problems or problems that can be understood by students in understanding narrative reading text in grade 4 in online learning at SDN Margorejo 1/403. This research uses a descriptive approach. Researchers used 40 grade 4B students and took 3 students as subjects. The techniques used by researchers used observation and tests. The observation method is used to measure students' understanding through learning what students understand from reading with the aspect of storytelling. While the test used for the 3 students explained the least amount of reading comprehension. The results showed that students experienced problems related to reading comprehension of narrative text where students did not understand the reading comprehension indicators: (1) the students had not been able to find the main idea of ​​the reading text (2) the students did not understand the information from the reading (3) the students had not been able to determine the facts and (opinion 4) students have not been able to conclude the reading. Suggestions for teachers to use better reading strategies and teachers to analyze reading. So that students are more careful in reading and make a corset to see the contents of the reading read.